2023
DOI: 10.1177/15459683231207360
|View full text |Cite
|
Sign up to set email alerts
|

Mild Stroke, Serious Problems: Limitations in Balance and Gait Capacity and the Impact on Fall Rate, and Physical Activity

Jolanda M. B. Roelofs,
Sarah B. Zandvliet,
Ingrid M. Schut
et al.

Abstract: Background After mild stroke persistent balance limitations may occur, creating a risk factor for fear of falling, falls, and reduced activity levels. Objective. To investigate whether individuals in the chronic phase after mild stroke show balance and gait limitations, elevated fall risk, reduced balance confidence, and physical activity levels compared to healthy controls. Methods An observational case-control study was performed. Main outcomes included the Mini-Balance Evaluation Systems Test (mini-BEST), T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Likewise, the correlation between AIS and susceptibility to head trauma is well exemplified. An observational study of individuals who experienced a minor AIS showed that these individuals were more than twice as likely to experience falls compared to healthy controls [ 109 ]. This study highlights the potential repercussions of a minor AIS on aspects such as balance and gait capacity, confidence in balance, risk of falling, and daily physical activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the correlation between AIS and susceptibility to head trauma is well exemplified. An observational study of individuals who experienced a minor AIS showed that these individuals were more than twice as likely to experience falls compared to healthy controls [ 109 ]. This study highlights the potential repercussions of a minor AIS on aspects such as balance and gait capacity, confidence in balance, risk of falling, and daily physical activities.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy finding from this study is that even individuals who had fully recovered displayed inferior balance and walking capacities compared to healthy controls. These results suggest that balance and walking ability after a minor AIS could be influenced by clinically imperceptible leg motor impairments or higher-level sensorimotor coordination, both of which pose a substantial risk for falls [ 109 ]. With twice more falls in this mild AIS cohort, the balance and gait impairments are clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of walking and balance functions represents one of the most common clinical manifestations of stroke, significantly increasing the risk of falls among stroke patients [5], thereby profoundly affecting their quality of life and their ability to reintegrate into society [6]. Therefore, restoring the walking ability of patients stands out as a primary objective in stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%